Chapter Japanese shōjin ryōri: the green competition from Buddhist temples to TV shows - GHIDINI, Chiara (Studi e saggi, 2021)
Registered in 2013 by the United Nations Education, Scientific and Cultural Organization (UNESCO) as Intangible Cultural Heritage, washoku, the "traditional dietary cultures of the Japanese," includes the so-called shōjin ryōri, an expression dated to the early modern period and related to the Buddhist avoidance of meat eating. Since its early appearance, shōjin ryōri has undergone a variety of changes, and its evolution up to contemporary times is relevant to Japan's cultural history. Traditionally, vegetables (sōjimono) were not thought of as precious or tasty ingredients. However, during the Kamakura period (1185-1333), the introduction of vegetarian dishes made to resemble fish and fowl, both in shape and flavor -- the so-called modoki ryōri-- attracted people's attention, contributing to the spread within Kyoto and the Japanese archipelago of a tastier and aesthetically pleasing Buddhist vegetarian cuisine. Throughout the 15th century local specialties and banquet cooking culture were extremely important: mountain products were generally still deemed inferior compared to sea and river ones, but in a text belonging to the irui gassen mono genre, the Shōjin gyorui monogatari, the reader witnesses the triumph of vegetables over the army of fish and animals. During the Meiji era (1868-1912), Buddhist vegetarianism faced the rise of a different culinary culture, whereby eating (beef) meat turned into a symbol for physical strength, both the individual one of young male citizens and the collective one of Japan as a new-born nation. Even part of the Buddhist clergy chose to embrace the meat-eating culture. Today, shōjin ryōri coexists with vegetarian choices based on different theoretical tenets and is promoted by NHK Television within programs designed for a global audience and aimed to advocate the Cool Japan strategy as well as in TV shows like Yamato amadera shōjin nikki, focused on the everyday (cooking) life of Buddhist nuns in a secluded temple within Nara prefecture. While encouraging local (and Buddhist) vegetarian food literacy, this program also fulfills the government agenda in terms of rural rejuvenation policies and the promotion of washoku (which includes shōjin ryōri) as a brand to be popularized both within and outside Japan.